New Roles for Old Glue: Astrocyte Function in Synaptic Plasticity and Neurological Disorders - Hussaini, Syed M. Q. (Int Neurourol J, 2018)
Previously believed to solely play a supportive role in the central nervous system, astrocytes are now considered active players in normal brain function. Evidence in recent decades extends their contributions beyond the classically held brain glue role; it’s now known that astrocytes act as a unique excitable component with functions extending into local network modulation, synaptic plasticity, and memory formation, and postinjury repair. In this review article, we highlight our growing understanding of astrocyte function and physiology, the increasing role of gliotransmitters in neuron-glia communication, and the role of astrocytes in modulating synaptic plasticity and cognitive function. Owing to the duality of both beneficial and deleterious roles attributed to astrocytes, we also discuss the implications of this new knowledge as it applies to neurological disorders including Alzheimer disease, epilepsy, and schizophrenia.